Larangan Praktik Monopoli dan Persaingan Usaha Tidak Sehat ditinjau dari Hukum Bisnis - Pribadi, Denny Slamet (Jurnal Aplikasi Manajemen, 2008)
Vast business development in Indonesia has caused the rise of business groups conglomeration. This phenomena brings both positive and negative social-economic impacts. The negative is that costumers, small and middle class business players becoming weakened. Monopoly and trust has been a crucial problem in this country. The larger the company, the larger its possibility to be involved in monopoly. Big companies and their conglomerations acquisited almost entire markets and therefore prohibited some new entry barriers consisted of middle-lower business players from entering the markets. The monopoly would have been formed when a company or a group of companies had aquisited 40% of the market. Law No 5 Year 1999 On Monopoly Prohibition and Unhealthy Business Competition, in general contains 6 parts of regulations: on prohibited types of husiness contracts, prohibited activities, dominant position, the foundation of Business Competition Monitoring Commission (KPPU), law enforcement and some other rules. This article seeks to describe several aspects of efforts for preventing unhealthy business competition through law and regulation in order to create a fair and condusive business atmosphere.